2016
DOI: 10.1016/j.conbuildmat.2016.03.200
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory evaluation of warm mix asphalt incorporating high RAP proportion by using evotherm and sylvaroad additives

Abstract: 8Warm mix asphalt (WMA) has gradually become more popular in the roading industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(10 citation statements)
references
References 7 publications
(1 reference statement)
1
9
0
Order By: Relevance
“…Different WMA technologies use additives or foamed bitumen to decrease mixing and compaction temperatures of asphalt. Experimental results showed that an Evotherm ® WMA incorporating 50% and 75% RAP displayed better performance in terms of ITS, dynamic modulus and rutting compared to a control mix and several WMA samples incorporating 25% RAP [22]. Furthermore, Martinho et al [23] found that WMA samples produced with different WMA additives including Sasobit ® , Rediset ® and Viatop ® , each incorporating 35% RAP, showed comparable fatigue performance to traditional hot mixed asphalt without RAP.…”
Section: Recycled Asphalt Pavementmentioning
confidence: 99%
“…Different WMA technologies use additives or foamed bitumen to decrease mixing and compaction temperatures of asphalt. Experimental results showed that an Evotherm ® WMA incorporating 50% and 75% RAP displayed better performance in terms of ITS, dynamic modulus and rutting compared to a control mix and several WMA samples incorporating 25% RAP [22]. Furthermore, Martinho et al [23] found that WMA samples produced with different WMA additives including Sasobit ® , Rediset ® and Viatop ® , each incorporating 35% RAP, showed comparable fatigue performance to traditional hot mixed asphalt without RAP.…”
Section: Recycled Asphalt Pavementmentioning
confidence: 99%
“…A similar trend was reported by Gonzalez et al [39] and Silva et al [42] when they evaluated Cecabase RT for their research works. Dai Xuan and Saleh [45] observed similar viscosity values when using 0.5% Evotherm 3G in a laboratory study. Both additives showed a maximum reduction of (0.3 Pa.s) in viscosity.…”
Section: Binder Characterisationmentioning
confidence: 62%
“…Refs. [50,51] showed comparable performance results that were comparable to HMA for WMA-RAP using different additives, except for moisture susceptibility [50].…”
Section: Recommendationsmentioning
confidence: 81%